Raw Multi-Channel Seismic Shot Data from the Blake Ridge, offshore eastern North America, acquired during R/V Maurice Ewing expedition EW0008 (2000) ... - Holbrook, W.; Pecher, Ingo; Lizarralde, Dan (Interdisciplinary Earth Data Alliance (IEDA), 2016)
This data set was acquired with the LDEO Multi-Channel Seismic system of the R/V Maurice Ewing during expedition EW0008 conducted in 2000 (Chief Scientist: Dr. W. Steven Holbrook). These data files are of SEGY format and include Multi-Channel Reflection Seismic shot data that have not been processed. Data were acquired as part of the project: Three-Dimensional Structure and Physical Properties of a Methane Hydrate Deposit and Methane Gas Reservoir, Blake Ridge, and funding was provided by NSF grant: OCE99-10966. These data are cited by Hornbach et al., 2005 and Hornbach et al., 2008. ...